The prevalence, determinants, natural history and impact of atrial fibrillation and atrial flutter in patients with tuberculosis pericarditis - insights from the IMPI trial - Chishala, Chishala (Division of Cardiology, 2016)
Tuberculosis is the most common cause of pericarditis in Africa. The dual human immunodeficiency virus (HIV)-tuberculosis epidemics are major contributors to the burden of extra-pulmonary tuberculosis, including tuberculous pericarditis. Mortality rates remain unacceptably high. Atrial fibrillation (AF) is the most common sustained arrhythmia encountered in clinical practice. It is associated with increased cardiovascular mortality and morbidity, as well as complications related to thromboembolic disease and haemodynamic instability. Similarly, atrial flutter (AFL) is a common macro-reentry arrhythmia, often associated with AF and its complications. While there is a recognized association between atrial fibrillation and / or atrial flutter (AF/AFL) and tuberculous pericarditis, there are limited data regarding the prevalence, determinants, natural history, and outcomes of AF/AFL in tuberculous pericarditis. Hypothesis: In patients with tuberculous pericarditis, AF/AFL is common, and when compared to tuberculous pericarditis patients that are in sinus rhythm, is associated with increased morbidity and mortality. Aims In participants with tuberculous pericarditis enrolled into the Investigation of the Management of Pericarditis (IMPI) trial, we intend to: 1. Estimate the prevalence of AF/AFL 2. Describe the natural history of AF/AFL 3. Identify clinical, biochemical and, echocardiographic predictors of AF/AFL 4. Determine the clinical impact of AF/AFL.